African Americans and the Consequences of Discrimination - Howe, Esther; Hamilton, Julia (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Lookism: Bias Based on Appearance - Howe, Esther (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Responding to the Oppression of Addiction: Canadian Social Work Perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2010)
"Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community."–pub. desc.
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; faculty_collection; therapy; Social Work; Canada

The Roots of the Recovery Movement in Psychiatry: Lessons Learned - Davidson, Larry (Wiley-Blackwell, 2010)
Keywords: History; Social psychiatry; Community psychiatry; Humanistic psychotherapy; Recovery movement; dept.swk; faculty_collection

Bullying - Howe, E.; Haymes, E.; Tenor, T. (The School Practitioner's Concise Companion to Preventing Violence and Conflict, 2010)
This chapter reviews the most well-researched, evidence-based antibullying interventions: involvement of all the stakeholders in a school, prevention through life skills curricula, problem-solving approaches, and those that focus on rules and consequences. Two factors emerge with clarity: (1) the exact components of the program do not matter as much as the quality and thoroughness with which the interventions are implemented; and (2) given the potentially severe consequences of bullying, it is a moral imperative to continue to implement such programs and to formulate and revise the programs based on solid evidence. © 2008 by Oxford University Press, Inc. All rights reserved.
Journal Abbreviation: The Sch. Pract. Concise Companion to Prev. Violence and Confl.
Keywords: Anti-bullying; Bullies; Bullying; School policy; School safety; School violence; School-based intervention; dept.swk

The Roots of the Recovery Movement in Psychiatry - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (John Wiley & Sons, Ltd, 2010)
lessons learned from previous efforts with the goal of "getting it right" this time. In response to the common refrain that we know about and 'do' recovery already, the authors set the recovery movement within the conceptual framework of major thinkers and achievers in the history of psychiatry, such as Philippe Pinel, Dorothea Dix, Adolf Meyer, Harry Stack Sullivan, and Franco Basaglia. The book reaches beyond the usual boundaries of psychiatry to incorporate lessons from related fields, such as psychology, sociology, social welfare, philosophy, political economic theory, and civil rights. From Jane Addams and the Settlement House movement to Martin Luther King, Jr., and Gilles Deleuze, this book identifies the less well-known and less visible dimensions of the recovery concept and movement that underlie concrete clinical practice. In addition, the authors highlight the limitations of previous efforts to reform and transform mental health practice, such as the de-institutionalization movement begun in the 1950s, in the hope that the field will not have to repeat these same mistakes. Their thoughtful analysis and valuable advice will benefit people in recovery, their loved ones, the practitioners who serve them, and society at large. Foreword by Fred Frese, Founder of the Community and State Hospital Section of the American Psychological Association and past president of the National Mental Health Consumers' Association. © 2010 John Wiley & Sons, Ltd.
Keywords: dept.swk

The common factors model: implications for transtheoretical clinical social work practice. - Cameron, Mark; Keenan, Elizabeth King (Social Work, 2010)
Direct practice social workers today are challenged to address the requirements of the complex array of professional, organizational, institutional, and regulatory demands placed on them in the broader socioeconomic context of fewer resources and diminished public support for social welfare services in the United States. The common factors model provides an accessible, transtheoretical, empirically supported conceptual foundation for practice that may help to resolve this conundrum and support effective practice. Common factors are conditions and processes activated and facilitated by strategies and skills that positively influence practice outcomes across a range ofpractice theories. The model provides an expanded conceptualization of the "active ingredients" required for change to include a focus on conditions and processes as well as practice strategies and to focus on all who are involved in the work. The model is described and implications for practice are discussed.
32 citations (Crossref) [2023-10-31] Place: United States Cameron, Mark. Department of Social Work, Southern Connecticut State University, New Haven 06515, USA. cameronm3@southernct.edu
Keywords: *Models; Theoretical; *Social Work/mt [Methods]; Change; Common factors; Empirical; Humans; Professional-Patient Relations; Social Support; Social work practice; Transtheoretical; dept.swk

Navigating the ethical terrain of spiritually focused psychotherapy goals: multiple worldviews, affective triggers, and personal practices - Keenan, Elizabeth King (Smith College Studies in Social Work, 2010)
Constructing mutual, spiritually focused psychotherapy goals is a practice activity fraught with numerous ethical and countertransferential challenges. This article seeks to inform the thinking and enhance the ability of clinical social workers to engage in collaborative and responsive dialogues with their clients regarding the goals of spiritually focused clinical practice by (1) identifying the multiple value frameworks that influence decisions regarding practice goals, (2) articulating some of the ethical complexities and common countertransferential reactions associated with goal setting, and (3) providing self-reflection questions and guides to help therapists navigate the complexities of this material.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-323-659-562-624 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: Countertransference; Ethics; Goals; Piritually focused psychotherapy; dept.swk

Seeing the forest and the trees: using dynamic systems theory to understand “Stress and coping” and “Trauma and resilience” - Keenan, Elizabeth King (Journal of Human Behavior in The Social Environment, 2010)
Although research is beginning to capture the complex interactions of biopsychosocial variables operating within experiences of stressors and trauma, the bodies of research have remained largely separate and limited. This study describes a scaffold of factors and pathways based on principles from dynamic systems theories (DST) to organize the literatures on stress and coping and trauma and resilience. As a process model, DST provides the language to understand both impact and response to stressors and trauma: Not as a list of symptoms but as interactive processes within persons and between persons and their surroundings. © Taylor & Francis Group, LLC.
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-271-426-334-225 tex.type: [object Object]
Keywords: Complexity theory; Dynamic systems theory; Stress and coping; Trauma and resilience; dept.swk; peer-reviewed